PERBEDAAN DAYA HAMBAT ANTARA KITOSAN DENGAN KOMBINASI ANTIBIOTIK METRONIDAZOL-AMOKSISILIN TERHADAP Actinobacillus Actinomycetemcomitans PENYEBAB PERIODONTITIS AGRESIF - RAFIDA NUR FITRIA; Ade Ismail A.K; Rama Putranto; Ratnawati . (Jurnal Medali, 2013)
Chitosan is a natural biopolymer derived from chitin polysaccharides which has amine functional groups that able to lyse bacteria so it can functioning as an antibacterial. The aim of this study is to determine the difference between the inhibition of chitosan with a combination of antibiotics metronidazole-amoxicillin against Actinobacillus actinomycetemcomitans causes periodontitis aggressive.This research method used laboratory experimental in vitro by disc diffusion method. The research sample used pure cultures of Actinobacillus actinomycetemcomitans. There were 6 groups of materials, chitosan solution with a concentration of 0.5%, 1%, 1.5%, 2%, distilled water with a combination of antibiotics and six times repetition. The data analysis technique used in this study was the One-Way ANOVA test with a probability of p <0.05, then post hoc test was used to determine the differences effectiveness among variables.The results showed an average inhibition zone formed on the chitosan solution of 0.5%, 1%, 1.5% and 2% were of 10.53 mm, 15.47 mm, 17.50 mm and 19.35 mm . While the average inhibition zone of 11.03 mm antibiotic combination. In the post hoc test data note that only 0.5% chitosan group with a combination of antibiotics metronidazole-amoxicillin which has no significant difference with p value: 0.371 (p <0.5).The survey results revealed chitosan solution has the ability to inhibit the growth of Actinobacillus actinomycetemcomitans causes periodontitis aggressive line with increasing concentration. The effectiveness of chitosan with the lowest concentration of 0.5% is almost the same as the effectiveness of a combination of antibiotics and chitosan solution with a concentration of 1%, 1.5% and 2% had a strong antibacterial effectiveness that chitosan can be used as an alternative antibacterial aggressive periodontitis. Keywords: Chitosan, Combination Antibiotics, Actinobacillus actinomycetemcomitans, aggressive periodontitis